2016
DOI: 10.1093/icvts/ivw106
|View full text |Cite
|
Sign up to set email alerts
|

Length of second-order chordae as a predictor of systolic anterior motion of the mitral valve

Abstract: The two variables of the second-order chordae and the distance from the coaptation point to the septum were associated with an increased risk of the post-repair systolic anterior motion after mitral valve repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
1
3
0
1
Order By: Relevance
“…Although SAM is commonly relieved by intravascular volume loading, discontinuation of inotropic drugs, and administration of beta-blockers after weaning from cardiopulmonary bypass, some patients require additional re-repair or valve replacement [16]. Recent reports showed that 0.2% to 8.0% of patients had SAM after MV repair [17][18][19][20]. Our results also showed a similar rate of SAM, with 1.4% requiring additional re-repair and 3.0% relieved by volume loading.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Although SAM is commonly relieved by intravascular volume loading, discontinuation of inotropic drugs, and administration of beta-blockers after weaning from cardiopulmonary bypass, some patients require additional re-repair or valve replacement [16]. Recent reports showed that 0.2% to 8.0% of patients had SAM after MV repair [17][18][19][20]. Our results also showed a similar rate of SAM, with 1.4% requiring additional re-repair and 3.0% relieved by volume loading.…”
Section: Discussionsupporting
confidence: 77%
“…Thus, the differences in these definitions of SAM may have affected our results. However, several studies have shown that risk factors for SAM after MV repair include excess posterior leaflet tissue, a short distance between the leaflet coaptation and the interventricular septum, a thick basal interventricular septum, a long secondary chorda, inadequate resection of the posterior leaflet, and use of a small annuloplasty [17,18]. A recent report indicated that a shorter length of neochordal repair than the reference chorda may be a useful technique to prevent SAM [16].…”
Section: Discussionmentioning
confidence: 99%
“…46) Even after mitral valve repair, the length of the AML secondary chordae and the distance from the coaptation point to the IVS were associated with an increased risk of the postrepair SAM. 47) Ferrazzi et al reported muscular mitral-aortic discontinuity in five young patients with obstructive HCM and sarcomere mutations. A long muscular discontinuity displaced the AML toward the apex and could predispose to the development of LVOT obstruction.…”
Section: Abnormality Of Mitral Valve Chorda and Papillary Musclementioning
confidence: 99%
“…46) Even after mitral valve repair, the length of the AML secondary chordae and the distance from the coaptation point to the IVS were associated with an increased risk of the postrepair SAM. 47) …”
Section: Introductionmentioning
confidence: 99%
“…У 190 пациентов с болезнью Барлоу (миксоматозным изменением МК и удлинением передней створки МК) F. Roshanali et al (2016) поставили цель определить предикторы возникновения SAM по данным трансэзофагеальной ЭхоКС. Перед операцией по устранению митральной регургитации SAM обнаружили у 12 пациентов, при этом у них оказалась значительно (в 1,5 раза) большая длина передней створки МК (2,76 ± 0,15 мм против 1,83 ± 0,32 мм, р < 0,001), уменьшение минимального расстояния от точки кооптации створок МК до МЖП (2,18 ± 0,36 мм против 2,91 ± 0,36 мм, р < 0,001).…”
Section: цель работыunclassified